Reconsidering the Effect of Market Experience on the ''Endowment Effect'' - Engelmann, Dirk; Hollard, Guillaume (Econometrica, 2010)
Simple exchange experiments have revealed that participants trade their endowment less frequently than standard demand theory would predict. List (2003a) found that the most experienced dealers acting in a well functioning market are not subject to this exchange asymmetry, suggesting that a significant amount of market experience is required to overcome it. To understand this market-experience effect, we introduce a distinction between two types of uncertainty—choice uncertainty and trade uncertainty—both of which could lead to exchange asymmetry. We conjecture that trade uncertainty is most important for exchange asymmetry. To test this conjecture, we design an experiment where the two treatments impact differently on trade uncertainty, while controlling for choice uncertainty. Supporting our conjecture, we find that “forcing” subjects to give away their endowment in a series of exchanges eliminates exchange asymmetry in a subsequent test. We discuss why markets might not provide sufficient incentives for learning to overcome exchange asymmetry.